2019
DOI: 10.1093/jscr/rjz074
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral antrochoanal polyp: report of a new case and systematic review of the literature

Abstract: Antrochonal polyp (ACP) is a benign, rare, and generally unilateral tumor which originates from the maxillary sinus mucosa. Bilateral ACP is extremely rare. Only few cases have been documented in the literature until 2018. The authors report the case of a 44-year-old women, who presented with a bilateral progressive nasal obstruction for the past 2 years, slight headache and a decreased sense of smell has been started in last four months. Nasal endoscopy revealed pale polypoidal masses in nasal cavities, arisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…It was observed that all cases operated in our clinic between the years 2012 and 2016 due to anthrocoanal polyp were unilateral. It has been reported that an anthrocoanal polyp is more common in men and under 20 years of age (10,12). The results of our study show that anthrochoanal polyp is seen 2 times more common in men.…”
Section: )supporting
confidence: 60%
See 1 more Smart Citation
“…It was observed that all cases operated in our clinic between the years 2012 and 2016 due to anthrocoanal polyp were unilateral. It has been reported that an anthrocoanal polyp is more common in men and under 20 years of age (10,12). The results of our study show that anthrochoanal polyp is seen 2 times more common in men.…”
Section: )supporting
confidence: 60%
“…Antrochoanal polyps frequently present as a unilateral nasal mass. Very few articles in the literature have reported bilateral involvement (12,13,14).…”
Section: )mentioning
confidence: 99%
“…The matrix for organizing findings concerning 14 cases are found in the literature (Table 1) [8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Matrix Organizing Findings In 14 Casesmentioning
confidence: 99%
“…Bilateral forms are very rare [1][2][3][4][5][6][7]. Only 14 cases have been mentioned in the literature [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Diagnosis difficulty is generally due to the scarcity of this disease, and the similar clinical presentation of more frequent differential diagnosis [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation